Chemoresistant pleomorphic rhabdomyosarcoma: whole exome sequencing reveals underlying cancer predisposition and therapeutic options. Issue 2 (23rd October 2018) - Tlemsani, Camille; Leroy, Karen; Gimenez-Roqueplo, Anne-Paule; Mansuet-Lupo, Audrey; Pasmant, Eric; Larousserie, Frederique; Boudou-Rouquette, Pascaline; Vidaud, Michel; Cadranel, Jacques; Blons, Helene; Goldwasser, Francois; Laurent-Puig, Pierre
Abstract : Background: Rhabdomyosarcoma (RMS) is rare cancer affecting children and adults. Pleomorphic RMS histology is almost exclusive to adult patients and often resistant to chemotherapy. Objective: We report the case of a 19-year-old patient who presented with a metastatic chemoresistant pleomorphic RMS. Methods: Considering the poor prognosis and the few systemic therapeutic options, we decided to carry out a whole exome sequencing (WES) of the tumour and germline DNA. Results: WES identified a germline variation (c.1863_1864insT) in the MLH1 gene corresponding to a pathogenic mutation: (p. Leu622Serfs*10), whereas the family history did not fit with classical criteria for Lynch syndrome. Loss-of-heterozygosity at MLH1 locus was found in the tumour. Immunohistochemistry showed loss of MLH1 and PMS2 nuclear expression in the tumour cells. In view of the mismatch repair defects and a high programmed cell death ligand 1 (PD-L1) expression (60% of tumour cells expressed PD-L1), we administrated an anti-PD-1 antibody to the patient. He achieved a rapid complete response of the lung metastases, which appears sustained after a 1-year follow-up. Conclusion: This observation of an RMS revealing an unexpected Lynch syndrome underlines the overlap between tumorous and germline molecular genetics and emphasises the major impact of cancer genomic medicine in clinical practice for guiding treatment decision.